Patagonia: A paleozoic continent adrift? - Ramos, Victor Alberto (Journal of South American Earth Sciences)
The evolution of Patagonia as an independent and exotic microcontinent from the rest of South America was a recurrent hypothesis since the XIX century, reaching notoriety during the discussion times of continental drift theory. The arrival of plate tectonics triggered different hypotheses, some of them with fixist interpretations that consider Patagonia as an autochthonous part of Gondwana, and others more mobilistic that postulate an allochthonous origin. After several decades, although some consensus exists among those hypotheses that postulate its allochthony, there is no agreement in its boundaries, subduction, accretion, and final amalgamation times to the Gondwana supercontinent. In this review the different magmatic belts are analyzed, their deformation and metamorphism, the associated sedimentary basins, as well as the existing geochronologic controls. Aware that important uncertainties still remain, a new model is proposed with two magmatic arcs: a western belt that was active from the Devonian to the mid Carboniferous, and a northern one partially coeval that led to the collision of Patagonia against the southwestern margin of Gondwana in the Lower Permian. It is hypothesized that the termination of the western magmatic arc activity was linked to the collision of the Antarctic Peninsula and associated terranes. The reconstruction of the plate tectonic history of Patagonia during the Paleozoic shows the existence of several episodes of fragmentation and rifting, convergence and accretion, renewed periods of rifting and reaccretion to the Gondwana margin. Those processes were intrinsic to the formation of Terra Australis orogen, controlled by the absolute motion of the Gondwana supercontinent and guided by successive global plate reorganizations. Fil: Ramos, Victor Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y ...